Analysis of Coupling BeamsÃâÃâ Reliability On the Outrigger and Belt Truss 80 Stories Earthquake Resistance Building System by Using Average Seismic Coefficient - HALIM LEMENA (NIM : 25017032), MARCO
In general, super tall skyscrapers design must follow the minimum base seismic shear coefficient in order. Commonly, super tall skyscrapers have long structural period. This long period will give lower base seismic shear coefficient, which is inadequate with the minimum requirement. However, the design of super tall skyscraper using minimum coefficient application will result in conservative design. Therefore, the average base seismic shear coefficient applied to the design of the structure. This thesis will analyse the reliability of coupling beam in 80-stories skyscraper using average base seismic shear coefficient while the detailing of the element follows SNI 2847-2013. Coupling beam is a significant element to resist lateral force in super tall skyscraper structure. The analysis will use first order second moment method.